Saddam Hussein - Shields, Charles J., 1951- (Philadelphia, Pa. : Chelsea House Publishers, 2003)
Describes the life of the leader of Iraq, from his childhood, through his rise to power, the Iran-Iraq War, the Persian Gulf War, to his ongoing presidency
'The liberation of Kuwait has begun' --'He who confronts' -- Strongman -- The Iran-Iraq war -- The Persian Gulf war -- 1992-1996 : tug of war -- The weapons inspection game -- A regime change in Baghdad
References : p. 98-99
Keywords: Hussein, Saddam, -- 1937- -- Juvenile literature; Presidents -- Iraq -- Biography -- Juvenile literature; Presidents -- Iraq